2007
DOI: 10.1029/2007gl029479
|View full text |Cite
|
Sign up to set email alerts
|

Methane release below a tropical hydroelectric dam

Abstract: Tropical reservoirs upstream from hydroelectric dams are known to release significant amounts of methane to the atmosphere. Here we demonstrate that methane emissions downstream from hydroelectric dams can also be large. Emissions of CH4 downstream of Balbina reservoir in the central Amazon basin (Brazil) were calculated from regular measurements of degassing in the outflow of the turbines and downstream diffusive losses. Annual emissions from the reservoir surface and downstream from the dam were 34 and 39 Gg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
196
0
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(237 citation statements)
references
References 15 publications
8
196
0
23
Order By: Relevance
“…GHG emissions from the TGR received widespread attention following the controversial results reported by Chen and co-workers 17 . They estimated that the total CH 4 emission from the surface of the TGR was 3.6 Mg h -1 by assuming an emission rate (3.3 mg m -2 h -1 ) comparable to those of tropical reservoirs, which are known to emit more GHGs than those in other climatic zones 8,9,11,12 . They also reported that CH 4 was emitted at an average rate of 6.7±13.3 mg m -2 h -1 from the newly created marshes in the drawdown zone from July to September 2008, with the marsh area accounting for 19% of the total CH 4 emissions from the reservoir surface 17 .…”
Section: Ghg Emissions From the Tgrmentioning
confidence: 99%
See 2 more Smart Citations
“…GHG emissions from the TGR received widespread attention following the controversial results reported by Chen and co-workers 17 . They estimated that the total CH 4 emission from the surface of the TGR was 3.6 Mg h -1 by assuming an emission rate (3.3 mg m -2 h -1 ) comparable to those of tropical reservoirs, which are known to emit more GHGs than those in other climatic zones 8,9,11,12 . They also reported that CH 4 was emitted at an average rate of 6.7±13.3 mg m -2 h -1 from the newly created marshes in the drawdown zone from July to September 2008, with the marsh area accounting for 19% of the total CH 4 emissions from the reservoir surface 17 .…”
Section: Ghg Emissions From the Tgrmentioning
confidence: 99%
“…Carbon dioxide can be fixed to organic carbon through photosynthesis, whereas methane can be oxidized by methanotrophs as they migrate towards the surface and the rest can escape into the atmosphere by diffusion and bubbling (slow natural degassing through formation of bubbles) in reservoirs and downstream rivers 6,12 . In particular, significant CH 4 emissions occur when the methane-rich water from a depth below the thermocline (the thin transition zone that separates the warmer, mixed layer at the surface from the colder deep water) rushes through the hydropower turbines with the drastic changes in pressure and temperature 12 . Dissolved CO 2 and CH 4 can also be released into the atmosphere as the water from the top layer of the reservoir passes through the spillways, owing to intense turbulence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The deep water layers in the reservoir are usually rich in CO 2 and CH 4 concentration due to high mineralization rates and high water pressure (which give high gas solubility level). By passing through the turbines, the gases are exposed to low pressure and high temperature conditions and, together with turbulent action, rapid degassing and emissions to the atmosphere occur [60]. For this reason, water flow to generate energy in the turbine must not be obtained from deep water levels or lower parts of the reservoir.…”
Section: Hydropower and Climate Changementioning
confidence: 99%
“…They may also escape during the process of turbulent degassing of dissolved gases in the water as water flows through the turbine runner during operation [60,61]. The deep water layers in the reservoir are usually rich in CO 2 and CH 4 concentration due to high mineralization rates and high water pressure (which give high gas solubility level).…”
Section: Hydropower and Climate Changementioning
confidence: 99%